2011
DOI: 10.1111/j.1365-294x.2011.05106.x
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement selection acting on the European house mouse hybrid zone

Abstract: Behavioural isolation may lead to complete speciation when partial postzygotic isolation acts in the presence of divergent-specific mate-recognition systems. These conditions exist where Mus musculus musculus and M. m. domesticus come into contact and hybridize. We studied two mate-recognition signal systems, based on urinary and salivary proteins, across a Central European portion of the mouse hybrid zone. Introgression of the genomic regions responsible for these signals: the major urinary proteins (MUPs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 146 publications
(381 reference statements)
4
76
0
Order By: Relevance
“…The result is to limit gene exchange between subspecies where they meet [43,44], reviewed in [29]. There is evidence that, in doing so, ABP comprises a system of incipient reinforcement where subspecies make secondary contact at the house mouse hybrid zone in Europe [45]. A recent study has presented evidence that the Abp genes expressed in mouse tears are a paralog group completely different than the smaller group expressed in saliva and that this may be due to subfunctionalization following duplication in Abp gene history [21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result is to limit gene exchange between subspecies where they meet [43,44], reviewed in [29]. There is evidence that, in doing so, ABP comprises a system of incipient reinforcement where subspecies make secondary contact at the house mouse hybrid zone in Europe [45]. A recent study has presented evidence that the Abp genes expressed in mouse tears are a paralog group completely different than the smaller group expressed in saliva and that this may be due to subfunctionalization following duplication in Abp gene history [21].…”
Section: Resultsmentioning
confidence: 99%
“…There is already substantial direct evidence for this from behavioral testing with saliva targets from congenic strains [43,44,45,53], and strong indirect evidence for tear ABP expressions, including observations of significant sex-limited expression of many paralogs and molecular evolutionary data for rapid evolution of Abpbg s in tears [21] and saliva [54]. There are six Esp s expressed in tears but they do not include Esp1 encoding the protein affecting lordosis or Esp22 , found to be released specifically into juvenile tear fluids (we studied adult mice).…”
Section: Resultsmentioning
confidence: 99%
“…Humans are one of the few mammals without a pelage of fur or wool covering nearly the entire body and thus the potential roles of proteins involved in grooming and pelage maintenance are not included in most human-centric discussions of saliva constitution. For example, we have previously shown that mice coat their pelts with salivary androgen-binding protein (ABP;[12]) and we suggested that this was a means of advertising the subspecies of the animal since ABP has been implicated in mediating subspecies identification[12-15]. A general role in coating surfaces was later proposed for secretoglobins such as ABP by Dominguez[16] following the first report of substantial identities among rabbit uteroglobin, cat Fel dI and mouse ABP by Karn[17].…”
Section: Results S and Discussionmentioning
confidence: 99%
“…In addition to or instead of that function, we proposed that their sex-limited expression, coupled with their rapid evolution may be clues to an as-yet-undetermined interaction between the sexes[2]. The three androgen-binding protein (ABP) subunit proteins, which form dimers to produce mouse pheromones (reviewed in[21]), are found in both sexes of mice and have been proposed to be involved in incipient reinforcement where subspecies of mice make secondary contact[15]. Mice also secrete trypsinogen, a peptidase inhibitor, MUP5, EGF binding protein, vomeromodulin, a glycoprotein and two poorly characterized proteins.…”
Section: Results S and Discussionmentioning
confidence: 99%
“…Populations of both subspecies at the border of the hybrid zone display assortative mate preference for signals present in the urine, and reproductive character displacement (for both preferences and signals) was documented between border and allopatric populations of the two subspecies in male and female mice [16,34,35]. The cline of transition of preferences of wild hybrids from one parental odour type to the other was found to be steep, coincident with the centre of the genetic cline in a Czech transect [35], but shifted roughly 10 km into the musculus territory in a Danish transect [16].…”
Section: Introductionmentioning
confidence: 99%